TINGKAT DEPRESI PENDERITA DIABETES MELLITUS DI PUSKESMAS GAYAMAN KECAMATAN MOJOANYARÂ KABUPATEN MOJOKERTO - Zainuri, Imam; Maharani, Sri (JURNAL KEPERAWATAN SEHAT, 2014)
Depression is one of the pressures that can aggravate diabetes. According Diabetes mellitus can be influenced by two factors consist of physical factors and psychological factors. Where physical factor is due to obesity (obesity), while psychological factors caused by negative thought patterns about themselves associated with the illness, and stress. Of the two factors will lead to the occurrence of depression in patients with diabetes mellitus, this study aims to determine the level of depression with diabetes mellitus. This study used a descriptive research design, the population of all patients with diabetes mellitus in sub-district health centers Mojoanyar Gayaman Mojokerto totaling 37 people, using a consecutive sampling technique. Consecutive sampling as many as 15 respondents sample instrument used in the form of a questionnaire sheet, data processing through the stages of Editing, Coding, Scoring, and Tabulating. Then presented in the form of a frequency distribution. The result of the discussion about the level overview depression diabetes mellitus can be concluded that, most of the respondents levels of depression were as many as 10 people. Advised in patients with diabetes to stay fit, should not be too much thought because it can increase the incidence of depression, it is especially in patients who are less able to meet its needs itself. It is recommended for health workers to provide counseling and education to the people especially those suffering from diabetes mellitus on self-care, both physically and psychologically.Keywords: Diabetes Mellitus, Depression